CAN DOMESTIC VIOLENCE BE A MECHANISM OF TORTURE? AND WHAT WILL COADYUVATE TO REDUCE THE CRIMINAL POWER ABOUT VICTIMS? THE CASE Y.P. FROM LA PAMPA (Perspectivas de las Ciencias Económicas y Jurídicas, 2017)
In this paper we will try briefly to address the issue on the understanding of domestic violence by gender as one of the forms of torture and whether it may serve to reduce the punitive power materialized on victims of violence diachronic gender, the State obligations deriving from the proper understanding of the application of the law with a gender perspective in key human rights and especially the State's obligation to act with due diligence to prevent such violence will happen, fester and play, especially when they have already been identified and addressed by public bodies, even when the aggressors whatsoever individuals.Finally, we apply such standards to the case Y.P. occurred in La Pampa in 2012, in which we can see that there has been ineffective intervention of a multiplicity of pre judicial agencies in relation to the logic here discuss about effective prevention, investigation, punishment, reparationand eradication of such violence, then the realization of the criminal power over a woman victim of gender violence diachronic acted in his own hand against her attacker.
Keywords: domestic violence; gender; acces to justice